2015
DOI: 10.1038/hdy.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Measuring individual inbreeding in the age of genomics: marker-based measures are better than pedigrees

Abstract: Inbreeding (mating between relatives) can dramatically reduce the fitness of offspring by causing parts of the genome to be identical by descent. Thus, measuring individual inbreeding is crucial for ecology, evolution and conservation biology. We used computer simulations to test whether the realized proportion of the genome that is identical by descent (IBD G ) is predicted better by the pedigree inbreeding coefficient (F P ) or by genomic (marker-based) measures of inbreeding. Genomic estimators of IBD G inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
322
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(351 citation statements)
references
References 39 publications
(66 reference statements)
11
322
1
3
Order By: Relevance
“…Genomic approaches capture variation in realized inbreeding that is missed by pedigree analysis due to the stochastic effects of linkage and unknown common ancestors of parents (Franklin, 1977; Thompson, 2013). Thus, while deep and accurate pedigrees can often precisely measure individual inbreeding in species with many chromosomes and/or high recombination rates (Kardos et al., 2018; Knief, Kempenaers, & Forstmeier, 2017; Nietlisbach et al., 2017), genomic approaches are expected to more reliably measure inbreeding and inbreeding depression (Kardos, Luikart, & Allendorf, 2015a; Kardos et al., 2018; Keller, Visscher, & Goddard, 2011; Wang, 2016). Given that many studies have used only shallow pedigrees or few DNA markers, it is possible that power to detect inbreeding depression has been low; therefore, inbreeding depression could be more common, widespread, and severe than previously thought.…”
Section: Improving Downstream Computational Analysesmentioning
confidence: 99%
“…Genomic approaches capture variation in realized inbreeding that is missed by pedigree analysis due to the stochastic effects of linkage and unknown common ancestors of parents (Franklin, 1977; Thompson, 2013). Thus, while deep and accurate pedigrees can often precisely measure individual inbreeding in species with many chromosomes and/or high recombination rates (Kardos et al., 2018; Knief, Kempenaers, & Forstmeier, 2017; Nietlisbach et al., 2017), genomic approaches are expected to more reliably measure inbreeding and inbreeding depression (Kardos, Luikart, & Allendorf, 2015a; Kardos et al., 2018; Keller, Visscher, & Goddard, 2011; Wang, 2016). Given that many studies have used only shallow pedigrees or few DNA markers, it is possible that power to detect inbreeding depression has been low; therefore, inbreeding depression could be more common, widespread, and severe than previously thought.…”
Section: Improving Downstream Computational Analysesmentioning
confidence: 99%
“…Thus, the longer the genetic map of a genome, which directly corresponds with the expected number of crossovers in each meiosis, the smaller the Mendelian sampling noise (Hill and Weir, 2011;Wang, 2016). To our knowledge, all analytical analyses and most of the simulations so far have assumed a uniform distribution of crossovers along chromosomes (see, for example, Franklin, 1977;Stam, 1980;Hill and Weir, 2011;Kardos et al, 2015;Wang, 2016; but see Suarez et al, 1979 andLibiger andSchork, 2007 for Monte Carlo simulations on relatedness). Although this assumption holds more or less for the human genome (Matise et al, 2007), linkage maps from other species have shown that the distribution of recombination along chromosomes can be highly biased toward the telomeres (Gore et al, 2009;Backström et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This will introduce variation into our estimates of GWIBD which we call the marker sampling noise. Unlike the Mendelian sampling noise that is an inherent result of the meiotic process, the marker sampling noise is only a consequence of the limited number of markers used; hence, the precision of GWIBD estimates increases when more molecular markers are sampled Kardos et al, 2015;Wang, 2016). Meiotic recombination also influences Marker F (Wang, 2016): given a fixed number of markers, the precision of Marker F decreases with the amount of meiotic recombination (whereas precision of Pedigree F increases), because each marker contains less information about GWIBD in genomes with more independently segregating segments (that is, longer genetic maps; Wang, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations